PENGEMBANGAN MODUL PENANGANAN KESEHATAN MENTAL BERBASIS KOMUNITAS DI KABUPATEN MALANG - Walda Isna Nisa (Jurnal Psikohumanika, 2021)
Abstract Mental disorders generally occur due to pressure that comes from external factors. Therefore, practical knowledge about mental disorders should also be understood by society. The community is expected to be able to participate through community empowerment methods to increase independence in handling mental health, so that there are no more mental patients who are in shackles and lose their productivity. This study aims to obtain an overview of the implementation of mental health first aid in the Bantur community which is packaged in the form of modules. The method used in this research is R&D with the following stages: 1) Problem identification, 2) Data collection, 3) Product design, 4) Product development, 5) Product validation and evaluation, 6) Dissemination and implementation, 7) Mass product manufacture. The research was conducted in Bantur District, Malang Regency. The research subjects were people who had involvement in various cases of mental disorders. Based on the results of the group test validity, 81% of 10 people chose that the module was feasible. In addition, the results of the expert validation of this module are included in the criteria "Appropriate to Use". After dissemination with 30 participants, it was found that the pre-test results were 60.3 and the post-test 64.37 with a significance of 0.000 <0.05, which indicated that there were significant differences in the participants' understanding before and after the socialization of the module. So it can be concluded that this Community-Based Mental Health Management Module is feasible and effective to use.